Residential Environment and Quality of Urban Life - Salihoglu, Tayfun; Turkoglu, Handan (Yildiz Technical Univ, Fac Architecture, 2019)
Quality of urban life is a multifaceted construct related with the multiple disciplines were born in a time that economy-centric policies were inadequate to solve social and environmental problems. The research area developed along with Social Indicators Movement. As an umbrella term quality of life contains different levels of qualities in different life domains. Because of the concepts like life and quality are highly intangible, discussion on the measurement and indicators which quality of urban life should include never reach an agreement. Quality of urban life that intents to explain people's life experience from the space perspective, is stressed in most of the urban studies as a level which should be increased for the sake of city and citizens. There are studies on type of indicators, measurement scales and approaches to quality of urban life. Studies on quality of urban life in residential level are more common in the literature, because of the place perception, evaluation and satisfaction of people is primarily experienced in their micro environment. Case studies on the relationship between residential environment and quality of life gained momentum since 2000's around the globe including Istanbul. Common trait in these studies is that residential quality of life research should be periodically remaked. The aim of this study is to explain the relationship between residential satisfaction and quality of urban life in Istanbul. The data used in the study is obtained both from the household surveys and expert observations which are conducted in the sampled residential areas. In this way, the research is designated as recommended in the literature that quality of life studies should include both subjective perceptions and objective indicators. Besides the relational findings between variables, results also include the spatial and individual differences in Istanbul and its citizens.
Keywords: Istanbul; quality of urban life; residential satisfaction; residential environment; quality of Life